Phytoplankton succession from 1968 to 1990 in the subarctic Lokka reservoir - Lepistö, Liisa (National Board of waters and the Environment. Vesi- ja ympäristöhallitus, 2011)
Tiivistelmä: Kasviplanktonin kehitys vuosina 1968-1990 subarktisessa Lokan tekoaltaassa